(untitled) (Research, Society and Development, 2022)
Introduction: When an offense is committed, the underage receives punishment with socio-educational measures. These measures have the objective to reinsert the young in the society. So, the health education has a primary roll to give knowledge about good habits for a better quality of life to the socioeducacional teenagers. AIMS: To highlight the impact of health interventions related to self-care among adolescents who are under socio-educational measures. Method: This is field research, whose results were obtained through a self-administered questionnaire, before and after the presentation of an educational video on 3 themes: Sexually Transmitted Infections, personal hygiene and drug use. Results: The results obtained demonstrate a basic knowledge that already exists on the themes. With health education, some concepts were better consolidated, such as the understanding of adolescents about the functionality of the contraceptive pill. As for drug use, most adolescents showed concern about their health and their family when talking about the subject. Related to personal hygiene, the socio-students demonstrate a consolidated idea about the concept of the subject in general. However, it was found that, despite being everyday topics, some important points were not well understood by the participants. Conclusions: The approach to everyday topics brought positive results for adolescents as well as for the institution, since the research evidenced the need to implement health education activities in a programmatic way, which will favor access to knowledge and consequently the promotion of self-care.